2010
DOI: 10.1021/mp1001922
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Metabolism of Radiolabeled Choline in Hepatocellular Carcinoma

Abstract: Objectives-Altered choline (Cho) metabolism in cancerous cells can be used as a basis for molecular imaging with PET using radiolabeled Cho. In this study, the metabolism of tracer Cho was investigated in a woodchuck hepatocellular carcinoma (HCC) cell line (WCH17) and in freshly-derived rat hepatocytes. The transporter responsible for [ 11 C]-Cho uptake in HCC was also characterized in WCH17 cells. The study helped to define the specific mechanisms responsible for radio-Cho uptake seen on the PET images of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Several in vitro studies on the metabolism of radiolabeled choline in tumor cells have suggested that phosphocholine produced from the phosphorylation of 14 C-choline is the main contributor of the observed tracer accumulation (20)(21)(22)(23). These studies closely agree with the results from our earlier in vitro study (24). In addition, a previous study on the in vivo distribution of fluorocholine in 9L-gliomabearing Fisher rats showed that up to 99% of tumor uptake was in the water-soluble fraction after 5 min after injection and that uptake became stable by 20 min after injection (20).…”
Section: Discussionsupporting
confidence: 90%
“…Several in vitro studies on the metabolism of radiolabeled choline in tumor cells have suggested that phosphocholine produced from the phosphorylation of 14 C-choline is the main contributor of the observed tracer accumulation (20)(21)(22)(23). These studies closely agree with the results from our earlier in vitro study (24). In addition, a previous study on the in vivo distribution of fluorocholine in 9L-gliomabearing Fisher rats showed that up to 99% of tumor uptake was in the water-soluble fraction after 5 min after injection and that uptake became stable by 20 min after injection (20).…”
Section: Discussionsupporting
confidence: 90%
“…Further incorporation of phosphocholine to membrane phosphatidylcholine is negligible within this time window (7,8,14,15). Chromatographic analysis also indicates that further betaine metabolism or conversion to acetylcholine is negligible (16,17).…”
Section: Introductionmentioning
confidence: 87%
“…11 C and 18 F-F-Cho PET Increased concentrations of choline have been confirmed in surgical HCC specimens [26]. In the hepatitis viral infection-induced woodchuck model it has been shown that HCC is associated with increased transport and phosphorylation of 11 C-Cho and that the increased accumulation of radiolabelled choline reflects increased phosphatidylcholine synthesis [27,28]. A study in the same animal model has shown a small preferential uptake of 11 C-Cho compared to 18 F-fluoroethylcholine in terms of tumour-to-background contrast [29].…”
Section: C-act Petmentioning
confidence: 94%